Acute Toxicity of Vildagliptin: Differences in Sensitivity between Cynomolgus Monkeys of Asian or Mauritian Origin. (January 2017) - Hoffmann, Peter; Martin, Lori; Keselica, Michael; Gunson, Diane; Skuba, Elizabeth; Lapadula, Dan; Hayes, Michael; Bentley, Phil; Busch, Steve
This article describes acute toxicity data in cynomolgus monkeys following oral treatment with vildagliptin, a dipeptidyl peptidase-4 inhibitor. Acute toxicity symptoms in cynomolgus monkeys include edema formation of the extremities, tails, and face associated with skeletal muscle necrosis, and elevations of lactate dehydrogenase, creatine kinase, alanine transaminase, and aspartate aminotransferase activities in the serum; hypothermia; hypotension; tachycardia; moribundity; and death in a few isolated instances. In surviving animals, symptoms were reversible even if treatment was continued. Cynomolgus monkeys from Mauritius appear more sensitive than monkeys of Asian origin. The underlying mechanism(s) of these symptoms in cynomolgus monkeys is currently not well understood, although a vascular mechanism including initial vasoconstriction and subsequent vascular leakage in distal extremities may play a role. The monkey data are reviewed and discussed in the context of other preclinical and clinical data, and it is concluded that acute toxicity following vildagliptin treatment is a monkey-specific phenomenon without relevance for humans.